Let's solve the equation step by step:
The given equation is: \[ 4x + 3(x - 2) = 8x - (6 + x) \]
First, we will simplify both sides of the equation.
-
Distributing \(3\) on the left side: \[ 4x + 3x - 6 = 8x - (6 + x) \] This simplifies to: \[ 4x + 3x - 6 = 8x - 6 - x \]
-
Simplifying both sides: The left side simplifies to: \[ 7x - 6 \] The right side simplifies to: \[ 8x - x - 6 = 7x - 6 \]
So now we have: \[ 7x - 6 = 7x - 6 \]
- Notice that both sides are equal: \[ 7x - 6 = 7x - 6 \]
This indicates that the equation is true for all values of \(x\). Therefore, we conclude that there are infinite solutions to the equation.
So, the correct response is: infinite solutions.